THE LANGUAGE OF MEDIA BETWEEN THE CLASSICAL LANGUAGE AND THE DIALECT - Abdul Mutaleb Al-Bakaa, Muhamad (ALBAHITH ALALAMI, 2005)
The media: ((Providing people with the right news, audio information, and constant facts that help them form a correct opinion in an incident or a problem, this opinion gives an objective expression of the mentality of the audience, their trends and tendencies). The German scientist Autogroot defines it as "the objective expression of the mentality of the audience, their spirit, their tendencies, and their trends at the same time." Whereas for "Aristotle", (Language) is a specific verbal system created as a result of an agreement between the members of the human group somewhere )). It is a symbol of thought, and a difference between humans and animals. Pronunciation and thought for “Aristotle” are intertwined: without pronunciation and without words, there is no thought or knowledge. The purpose of (language) for “Aristotle” is: achieving the links between humans, or having them knowing things, language may also be used as a tool for education and entertainment in a particular domain of human activity. As for its origin: (language) originated gradually, and did not happen all at once. Language spreads accordingly to the needs and perception. And the first words uttered by man are the words that express the closest things surrounding him and can be percepted visually. According to our arabic scientists, Ibn Juney said: “As of its meaning, it is voices told by each nation to express their needs”. In addition, Ibn al-Hajib said: "Language is every term for a meaning.” Most traditional scholars have considered that language is a human way to communicate thoughts, emotions, and desires, through a system of symbols that are produced in a narrative fashion . Some scholars have replied that language may be used to conceal thought. Therefore the phrase "The language is to be used to hide human thoughts" which is a famous quote in linguistic studies and from that we conclude that language is distinguished from other symbols and signatory systems because it is accessible and arising from society for society and begins with prose, then poetry arises.. Then comes the science of the creation of the tongue: which starts with extrapolation and tracking, conservation and codification, including vocabulary and compositions. After that comes meditation and the lesson to develop grammatical, linguistic laws and the writing industry. Language at the heart of a society is a way of (communication) or (transport) or (expression) through the (verbal voices), what the language gives or express, are the thoughts, meanings, emotions and desires or thought in general () . However, language can not be defined as a mere means of communication, because the study of word functions in any language does not support such a definition. And for that, one must say that The language was a function of communication. In other words, communication was one of the language’s functions. The old trend was to emphasize that language was the pot of thought, and that its function was to express human thought whether it was purely intellectual or related to emotions, sensations and human desires. Some modernists prefer the function of communication rather than the one of language.